Assessment of Bisphenol A and Heavy Metals in Some Commercial Brands of Canned Fish - Opatola, Segun F.; Akpambamg, V.O. E; Lere-Aliu, M. O. (Faculty of Pharmacy, Universitas Mulawarman, Samarinda, Indonesia, 75117, Gedung Administrasi Fakultas Farmasi Jl. Penajam, Kampus UNMUL Gunung Kelua, Samarinda, Indonesia, 2025)
Bisphenol A are commonly referred to as endocrine disruptive chemicals that migrates into food through canning. Even at low levels, they can result in a variety of health issues, Heavy metal toxicity has become a severe threat and is linked to a number of health risks. When fish are exposed to chemical pollutants, especially when being canned for preservation, bioaccumulation usually occurs. Acid digestion methods were used to measure the specified heavy metals in canned fish, and an atomic adsorption spectrophotometer was used to conduct the analysis. The results of Heavy metals show that Iron, copper and Zinc have the highest concentration indicating that the canned fish are rich in Iron, copper and Zinc, while Lead has the lowest concentration. For Bisphenol A, the concentration ranges from 0.019 to 0.403 ?g/g and satisfied this stipulated standard. Based on the results, the four selected heavy metals, Cu, Fe, Zn, and Pb, as well as Bisphenol A, have concentrations that are within WHO-acceptable levels in canned fish.